2015
DOI: 10.3807/josk.2015.19.3.311
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Temperature Dependence of Phosphor Conversion Efficiency in White Light-Emitting Diodes

Abstract: We investigate the temperature dependence of the phosphor conversion efficiency (PCE) of the phosphor material used in a white light-emitting diode (LED) consisting of a blue LED chip and yellow phosphor. The temperature dependence of the wall-plug efficiency (WPE) of the blue LED chip and the PCE of phosphor are separately determined by analyzing the measured spectrum of the white LED sample. As the ambient temperature increases from 20 to 80 o C, WPE and PCE decrease by about 4.5% and 6%, respectively, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 12 publications
(10 reference statements)
0
13
0
Order By: Relevance
“…Through the analysis of the equal proportion of the edge length of similar triangle and the analysis of the green and blue primary colors, it can be concluded that the target luminance should meet the requirements of formula (7).…”
Section: Proposed Algorithmmentioning
confidence: 99%
See 3 more Smart Citations
“…Through the analysis of the equal proportion of the edge length of similar triangle and the analysis of the green and blue primary colors, it can be concluded that the target luminance should meet the requirements of formula (7).…”
Section: Proposed Algorithmmentioning
confidence: 99%
“…According to the requirements of formula (7) and the calculation method of formula (5), it can be concluded that the PWM of the color compensation module should be revised as shown in formula (8).…”
Section: Proposed Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…However, due to the characteristics of phosphors, the material of phosphors is mainly YAG. The luminous efficiency of phosphor conversion materials varies at different temperature [7][8] . The emission of phosphor depends on the intensity of blue light and the conversion efficiency of phosphors.…”
Section: Because Of the Low Efficiency Of Green Light Serious Specklementioning
confidence: 99%